2016
DOI: 10.2494/photopolymer.29.459
|View full text |Cite
|
Sign up to set email alerts
|

Cover-layering a Porous Polyimide Flexible Print Circuit with a Porous Polyimide Layer

Abstract: Porous polyimide films are promising insulators for next generation electronic devices. Recently, we had developed a high-intensity UV exposure apparatus under a high-pressure CO 2 gas atmosphere for the production of porous polyimide films. In this study, the cover-layering process of a porous polyimide layer on two different types of flexible print circuits (FPCs) with insulation materials made of solid polyimide and porous polyimide was examined. Although a portion of the pores above and below the copper li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…This decrease effectively lessens the dielectric loss of high-frequency signal in the metal line on the porous polyimide substrate. The dielectric constant reduction has been investigated by several researchers, as summarized in prior studies [1,2] and reviews [3,4] and in our previous articles [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This decrease effectively lessens the dielectric loss of high-frequency signal in the metal line on the porous polyimide substrate. The dielectric constant reduction has been investigated by several researchers, as summarized in prior studies [1,2] and reviews [3,4] and in our previous articles [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The film was then used as cover layer for the micro strip line of the porous PI substrate. Moreover, copper plating was applied to the via hole of the porous PI film [7]. The aqueous solution of copper plating infiltrated into the porous structure as the pores were partially interconnected.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we tested the suitability of porous polyimide films for flexible printed circuits by subjecting them to cover-layering and copper plating [6]. The results showed that cover-layering induced the collapse of some pores, with copper plating leading to pore infiltration, indicating that such treatments require closed-pore films.…”
Section: Introductionmentioning
confidence: 99%
“…However, the increasing demand for mobile devices capable of faster data transfer requires the use of PI FPCs with low dielectric constants to decrease signal attenuation. Therefore, dielectric constant reduction has been investigated by several researchers, as summarized in prior studies [1,2] and reviews [3,4] and in our previous articles [5,6].…”
Section: Introductionmentioning
confidence: 99%